Synthesis and characterization of Palladium(II) and Nickel(II) complexes of schiff bases and the potential of the Palladium(II) complexes as Catalysts for C-C bond formation / Amalina Mohd Tajuddin - Mohd Tajuddin, Amalina (2014)
This study reports the synthesis, characterization and catalytic activities of palladium(II) Schiff base complexes, both as homogeneous and MCM-41 supported heterogeneous catalysts for cross-coupling C-C bond formation reactions. Three broad groups of inexpensive Schiff base ligands (LI, L2 and L3) have been synthesized through condensation process between four benzylamine derivatives with aldehyde or ketone in 1:1 molar ratio. 12 ligands and 20 metal complexes of Pd(II) and Ni(II) have been successfully obtained. The metal complexes were prepared through the complexation reaction between the Schiff base ligands with Pd(II) and Ni(II) acetates in a 2:1 molar ratio. All the synthesized ligands and complexes have been characterized using CHN elemental analysis, infrared, 'H and 13C NMR, UV-Visible, melting point determination, molar conductance and magnetic susceptibility. The molecular geometries of ten complexes namely PdLlc, PdLld, NiLlc, NiLld, PdL2a, PdL2d, PdL3b, PdL3c, PdL3d and NiL3d have been solved by single crystal X-ray crystallography. It revealed that these Schiff bases behave as bidentate ligands, coordinating through the imine N and phenolic O donor atoms, as also shown by the infrared data. Magnetic susceptibility suggests square planar Pd(II) and Ni(II) complexes, while non-electrolytic behaviour indicated the absence of ions in chloroform. PdL3a, PdL3b, PdL3c and PdL3d have been chosen to catalyze the Heck and Suzuki cross-coupling reactions because of their good performances in the screening phase. Three parameters have been chosen for optimization of the reaction conditions, which were types of bases, catalyst loadings and reaction temperatures. This study has found that the complexes performed well at a relatively low catalyst loading of 1 mmol%. They were effective catalysts for Heck reaction of iodobenzene with methyl acrylate to form methyl cinnamate and for Suzuki reaction of iodobenzene with phenylboronic acid to form 1 ,1 ’-biphenyl where the conversions of iodobenzene reached up to 100% at 100°C within 24 hours of reaction time. For the heterogeneous catalytic investigations, two modified MCM-41 moieties, namely MCM-41-Pd-Ovan and MCM-41-PdL3c, were investigated. The PdL3c complex was chosen for heterogeneous catalytic study due to its superior performance during homogeneous catalysis study. The synthesized MCM-41 supported species were characterized using CHN elemental analysis, ICP-OES, infrared, XRD, TGA-DTA, BET and nitrogen sorption and FESEM-EDX analyses. ICP-OES data revealed that the palladium loading in MCM-41-Pd-Ovan and MCM-41-PdL3c were 0.259 and 0.097 mmolg'1, respectively. Both were found to be moderately good catalysts. Some leaching of active species in reaction mixtures especially for the MCM-41-Pd-Ovan was detected. The leaching was found to be less extensive for the MCM-41 -PdL3c. As additional work in this study, six metal complexes namely PdLlc, PdLld, PdL3d, NiLlc, NiLld and NiL3d have undergone antibacterial investigation as a representatives group. The complexes have shown a little or no inhibition against E. coli, B. subtilis and S. aureus, most likely due to the low solubility of the complexes in DMSO solvent.